Efficacy of two plant powders as cowpea grain protectants against Callosobruchus maculatus Fabricius (Coleoptera, Chrysomelideae: Bruchinae) - CHOUGOUROU, CHÈPO DANIEL; AGOSSA, Christophe Homevo; ZOCLANCLOUNON, Yedomon Ange Bovys; NASSARA, Medewouin Genice; AGBAKA, ALPHONSE (My University, 2016)
Objective: This study was carried out to study insecticidal effect of powders from Chenopodium ambrosioides leaves and Aframomum melegueta seeds on cowpea weevil Callosobruchus maculatus. Methodology and Results: 5g of both powders of A. melegueta and C. ambrosioides were used in the propor- tions of C. ambrosioides 100%:A. melegueta 0%, C. ambrosioides 0%: A. melegueta 100%, C. ambrosioides 30%: A. melegueta 70%, C. ambrosioides 70%: A. melegueta 30% and C. ambrosioides 50%: A. melegueta 50%. Plant powders were added to 20g of cowpea grains. Bioassays were conducted at 26.64±0.74°C and 72.55±4.38% relative humidity. Insect mortality was evaluated from 24 to 144 hours after treatment. Results obtained indicated that plant powders had significant effect on C. maculatus mortality. The highest mortality rate (70.00±26.45%) was recorded in jar treated with C. ambrosioides. Conclusion and application of findings: Either plant powders, alone or mixed had high insecticidal effect on C. maculatus. Because of their effectiveness, these plant powders could be recommended as grain protectants against C. maculatus.
Keywords: Chenopodium ambrosioides; Aframomum melegueta; Callosobruchus maculatus; Insecticidal ac- tivity